DAMPAK PANDEMI COVID-19 DAN KEBIJAKAN PPKM TERHADAP TINGKAT PENDAPATAN USAHA KECIL DAN MENENGAH (UKM) DI WILAYAH BANJARBARU KALIMANTAN SELATAN - Periyadi Periyadi; Lamsah Lamsah; Muhammad Haris Syafitri (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The outbreak of the corona virus requires people to carry out activities at home to break the chain of virus spread in accordance with government policies. This policy ultimately makes many activities that require direct interaction to be avoided and limits people's activities from leaving their homes. Among the hardest hit are Small and Medium Enterprises, which are the drivers of the economy. Many small and medium businesses have temporarily closed their businesses. This study aims to determine whether there is an impact of the influence of Covid-19 and the PPKM Policy on the income level of SME business actors in the Banjarbaru City area. The method used in this research is quantitative research, which is a research model that requires the calculation of numbers, while the approach used is a survey approach, namely research that takes samples from the population and uses questionnaires as the main data collection tool. The results of this study indicate that the variables in the study have a significant effect.